Theoretical and experimental analysis of electromagnetic coupling into microwave circuit - Ilham Zerrouk; Mohamed Amellal; Amine Amharech; Mohamed Ramdani; Hassane Kabbaj (Institute of Advanced Engineering and Science, 2019)
In this paper, our work is devoted to a time domain analysis of field-to-line coupling model. The latter is designed with a uniform microstrip multiconductor transmission line (MTL), connected with a mixed load which can be linear as a resistance, nonlinear like a diode or complex nonlinear as a Metal Semiconductor Field-Effect Transistor (MESFET). The finite difference time-domain technique (FDTD) is used to compute the expression of voltage and current at the line. The primary advantage of this method over many existing methods is that nonlinear terminations may be readily incorporated into the algorithm and the analysis. The numerical predictions using the proposed method show a good agreement with the GHz Transverse Electro Magnetic (GTEM) measurement.